Optimalisasi Mutu Pendidikan melalui Administrasi Personalia yang Efisien: Pilar Utama Keberhasilan Institusi Sekolah - Fatimah, Meti; Bahij, Alfan; Nurachman, Azhar; Setiawan, Rizka (TSAQOFAH, 2024)
The quality of education in schools is largely determined by the effective management of educational and administrative staff. Personnel administration, which involves recruitment, training, career development, and performance evaluation, plays a pivotal role in ensuring that human resources (HR) in schools operate efficiently. Effective HR management enhances teacher performance and fosters a positive work environment, directly contributing to improved educational quality. Conversely, poor HR administration can lead to low teacher motivation, high turnover, and declining academic standards. As modern curricula and technological advancements evolve, personnel administration must adapt to ensure continuous professional development and well-being for educators. This article investigates the significance of personnel administration in improving school quality. By reviewing recent literature, it explores how recruitment, training, and performance evaluation processes impact teaching quality and student outcomes. The analysis also provides recommendations for policymakers to strengthen HR management in schools, ensuring sustained educational excellence. Structured personnel administration is shown to be essential for motivating teachers, enhancing performance, and ultimately raising the overall standards of education.